地域看護職が行う認知症高齢者のアドバンス・ケア・プランニング準備支援の検討—認知症初期集中支援チーム看護職の語りから - 菊本 由里; 徳重 あつ子; 岩﨑 幸恵 (日本看護科学会誌, 2023)
要旨　目的：地域看護職が行う早期支援における認知症高齢者のアドバンス・ケア・プランニング（ACP）準備支援を明らかにする．　方法：10施設・12名の地域看護職に半構造化インタビューを行い質的記述的に分析した．　結果：ACP準備支援は，【慎重な認知症診断・告知プロセスの検討】【本人の状況に適した生活を継続するための早期から切れ目ない支援】【認知症高齢者に対する家族の理解促進と困りごとの継続支援】【多職種・関係者協働のコーディネートとネットワークづくり】を実践していた．また地域看護職の多くは，早期のACPに関して，実施の難しさを感じていた．支援チームと兼務して長期にわたり支援の役割がある地域看護職は，ACPを意識しながらかかわりを持っていた．　結論：認知症高齢者のACP準備支援は，早期支援の中に含まれているものであり，意識してACPの準備性を高めていけるように進めていくことが必要である． 　Objective: Clarifying advance care planning (ACP) preparation support for older adults with dementia in early support provided by community nurses.　Methods: We conducted semi-structured interviews with 12 community nurses from 10 facilities and analyzed them qualitatively and descriptively.　Results: The ACP preparation support included "consideration of the dementia diagnosis/notification process," "continuous support from an early stage to continue a life suited to the person's situation," "promotion of family understanding of older adults with dementia and their troubles," and "Coordination and network building for multi-professional/related party collaboration." Many community nurses found it difficult to implement ACP at an early stage. Community nurses, who had a long-term support role concurrently with ACP were involved while being aware of ACP.　Conclusion: The ACP preparation support for older adults with dementia is included in early support, and it is necessary to consciously promote ACP readiness.